2014
DOI: 10.3389/fnmol.2014.00033
|View full text |Cite
|
Sign up to set email alerts
|

Tau-tubulin kinase

Abstract: Tau-tubulin kinase (TTBK) belongs to casein kinase superfamily and phosphorylates microtubule-associated protein tau and tubulin. TTBK has two isoforms, TTBK1 and TTBK2, which contain highly homologous catalytic domains but their non-catalytic domains are distinctly different. TTBK1 is expressed specifically in the central nervous system and is involved in phosphorylation and aggregation of tau. TTBK2 is ubiquitously expressed in multiple tissues and genetically linked to spinocerebellar ataxia type 11. TTBK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 86 publications
3
66
0
Order By: Relevance
“…From evolutionary perspective, TTBK2 is a member of casein kinase 1 (CK1) superfamily, its kinase domain shows 38% identity with CK1δ (30,31). Apart from TTBK2, additional kinase MARK4 has been implicated in cilium initiation and assembly, although it seems to control the processes via SDA rather than DA of mother centriole (32).…”
Section: Introductionmentioning
confidence: 99%
“…From evolutionary perspective, TTBK2 is a member of casein kinase 1 (CK1) superfamily, its kinase domain shows 38% identity with CK1δ (30,31). Apart from TTBK2, additional kinase MARK4 has been implicated in cilium initiation and assembly, although it seems to control the processes via SDA rather than DA of mother centriole (32).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that TTBK1 is co-localized with pS422 + pTau in neuronal cell soma containing pre-tangles but not in neuropil threads or neurofibrillary tangles [8]. Since TTBK1 can directly phosphorylate tau at S422, this data suggest its role in pS422 + pTau accumulation in pre-tangle + neurons [6,43].…”
Section: Discussionmentioning
confidence: 88%
“…Using computational algorithms for microRNA target prediction 18 on all known tau kinases (i.e. Cdk5, GSK3, MARK, PKA, AMPK) 17,19,20 revealed only three kinases are predicted targets for miR-219 and highly conserved in both humans and rodents (mouse and rat), Tau tubulin kinase 1 (TTBK1), Calcium/calmodulin-dependent protein kinase 2 gamma subunit (CAMK2) and Glycogen synthase kinase 3 beta (GSK3) ( Supplementary Figure 1), which are all implicated in the generation and/or accumulation of abnormal hyperphosphorylated tau [21][22][23][24][25] . Importantly, miR-219 is not predicted to bind to the 3'UTR and repress expression of any known tau phosphatases 26 .…”
Section: Resultsmentioning
confidence: 99%